Study of prone positioning to reduce ventilator-associated pneumonia in hypoxaemic patients - Mounier, R; Adrie, C; Français, A; Garrouste-Orgeas, M; Cheval, C; Allaouchiche, B; Jamali, S; Dinh-Xuan, A T; Goldgran-Toledano, D; Cohen, Y; Azoulay, E; Timsit, J-F; et al. (The European respiratory journal, 2010)
The aim of the present study was to examine whether prone positioning (PP) affects ventilator associated-pneumonia (VAP) and mortality in patients with acute lung injury/adult respiratory distress syndrome. 2,409 prospectively included patients were admitted over 9 yrs (2000-2008) to 12 French intensive care units (ICUs) (OUTCOMEREA). The patients required invasive mechanical ventilation (MV) and had arterial oxygen tension/inspiratory oxygen fraction ratios <300 during the first 48 h. Controls were matched to PP patients on the PP propensity score (+/-10%), MV duration longer than that in PP patients before the first turn prone, and centre. VAP incidence was similar in the PP and control groups (24 versus 13 episodes.1,000 patient-days MV(-1) respectively, p = 0.14). After adjustment, PP did not decrease VAP occurrence (HR 1.64 (95% CI 0.70-3.84); p = 0.25) but significantly delayed hospital mortality (HR 0.56 (95% CI 0.39-0.79); p = 0.001), without decreasing 28-day mortality (37% in both groups). Post hoc analyses indicated that PP did not protect against VAP but, when used for >1 day, might decrease mortality and benefit the sickest patients (Simplified Acute Physiology Score >50). In ICU patients with hypoxaemic acute respiratory failure, PP had no effect on the risk of VAP. PP delayed mortality without decreasing 28-day mortality. PP >1 day might decrease mortality, particularly in the sickest patients.